Pradigma Pendidikan Dalam Al-Qur‟an: Menganalisis Profil Guru Dalam Perspektif Al-Qur‟an - Azahra, ‎ Fatma; Charles, Charles (ANTHOR: Education and Learning Journal, 2022)
Educators as the most important component in the world of education become figures in theirenvironment in delivering their students a brighter future. Educators as the spearhead insuppressing ignorance and immorality, of course, must have Qur'anic characteristics persuasively and constructively. If in the Al-Qur'an at least four classifications of educators are mentioned, basically they have "similarities" in coaching students according to their respective objects and end in enforcing sentenceullah. As for the sincerity of educators in the Qur'an, not to expect anything in transferring their knowledge to others, of course, this needs to be instilled in an educator from an early age. But as an educator, he has two obligations at the same time. On the one hand, educators should convey their knowledge, and educate the community, while on the other hand, they should continue their life. So that these two concurrent obligations must be fulfilled without reducing the sincerity recommended in the Qur'an. Thus educators in the Qur'an are the determinants of the goodness of the future young generation because it is in the hands of educators that the younger generation will become a generation that is strong and ready to continue the relay of future leaders with a morepeaceful future by the teachings of the Qur'an an.